Should the Philippines Adopt Net Neutrality Regulations? - Ramonette B. Serafica; Queen Cel A. Oren (Philippine Institute for Development Studies (PIDS), 2023)
Net neutrality has been one of the most controversial issues in internet regulation. Currently, there is no policy or regulation on net neutrality in the Philippines. This might change, however, with the inclusion of paid prioritization and throttling among the prohibited acts in the proposed Open Access in Data Transmission Act. Based on a review of the economic arguments and approaches adopted in other countries, integrating net neutrality principles in the proposed legislation could lead to unintended consequences that may hinder the growth of the data transmission industry. Instead, a separate measure could be introduced, if deemed appropriate, after careful study.
Keywords: 330; internet; network; neutrality; non-discrimination